CHATGPT IN ACADEMIC WRITING: EFL PRE-SERVICE TEACHERS’ POINTS OF VIEW - Narisha Nur Azizah; Saffanah Navya Sadifah; Dea Priana Wati; Misdi Misdi; Dwiniasih Dwiniasih (Universitas Wiralodra, 2025)
Based on recent developments, artificial intelligence (AI) has transformed the way second language writing is taught. ChatGPT, as a current AI tool, is seen as a potential writing assistant for students. This study explores how university students evaluate ChatGPT when writing academic papers. Employing a qualitative case study, data were collected from six female undergraduate English language education students enrolled in an academic writing course at a private university in West Java, Indonesia, through interviews, reflective diaries, and classroom observations. The findings show a shift in students’ perceptions, from initial doubts to recognizing practical benefits. Many students initially struggled to begin writing due to difficulties generating ideas or forming sentences. After being introduced to ChatGPT, they used it to draft opening paragraphs, check grammar, and explore concepts. Students reported improved ability in structuring thoughts and overcoming writer’s block, leading to more coherent writing. However, some expressed concern about overreliance, fearing it might hinder critical thinking and creativity. The study concludes that while ChatGPT offers substantial support, it should be used as a complementary tool. Educators are encouraged to guide students in leveraging AI to enhance rather than replace their writing skills.